SUPERVISI PENDIDIKAN DALAM MENGEMBANGKAN KOMPETENSI GURU MATEMATIKA PADA MADRASAH ALIYAH NEGERI (MAN) BEUREUNUEN KABUPATEN PIDIE - Khazanatul Khairat (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2013)
Teaching supervision is one of factors influencing the development of teacher’s competence. This research used descriptive qualitative method. The data were collected through observation, interview and documentation. The subject of this research were the supervisors, principal, vice principal of curriculum affairs, math teachers, and chief of MGMP. The results of this research showed that (1) annual supervision program was compiled both for regency and municipality level by several supervisors employed by the coordinator of supervisor based on his authority that it then became a reference for supervisors in the area to compile semester program. (2) Techniques of supervision of education conducted by supervisors were class visit, class observation, orientation meeting, teacher meeting and sharing knowledge. The supervision conducted periodically based on supervision program. (3) The strategies used by supervisors in running their duties were collecting sample at each school, forming team teaching, and delegating vice principal and chief of MGMP. (4) The supporting factors were teachers’ willingness to be supervised and principal’s enthusiasm in supervising. On the other hand, the inhibiting factors were elderly supervisors recruited nearly retired, the amount of supervisors and teachers were disproportionately so that the supervision towards teachers were not balanced and there was no distribution of supervisors based on their background study.